New Drugs in the Treatment of Elderly Patients with Metastatic Castration-Resistance Prostate Cancer. Issue 4 (July 2016) - Genestreti, Giovenzio; Di Battista, Monica; Cavallo, Giovanna; Brandes, Alba A.
Treatment of prostate cancer is continually evolving and new therapies have become available. However, the management of elderly patients is challenging due to their age and comorbidities. Androgen deprivation therapy remains the mainstay treatment of hormonal-sensitive disease. Nevertheless, when disease becomes resistant to castration, docetaxel-based chemotherapy represents the standard rescue therapy irrespective of patient age. Recently, chemotherapeutic agents such as cabazitaxel and hormonal therapies such as abiraterone acetate and enzalutamide have been shown to improve survival in patients with progression of disease before or following docetaxel. This review focuses on the safety and efficacy results of these new drugs in elderly patients.